A study of blood stream infection in Neonates - P.MAHARAJA; P.SEKAR (International Journal of Pharma and Bio Sciences, 2017)
To study the prevalence of neonatal sepsis in new born babies in SRM Hospital. The present study is aimed to isolate and identify the microbial isolates(bacteria & fungi) responsible for neonatal sepsis by conventional blood culture methods. The prospective study was conducted in 84 neonates, fulfilling the inclusion and Exclusion criteria subjected to sepsis screening. Blood Culture and sepsis screening was carried out in 84 neonates. Out of 84 neonates with clinical features of sepsis, 7 had positive blood culture and 77 had negative blood culture. Sepsis screening was carried out with total leucocytes count, absolute neutrophils count, CRP and Thromphocyte estimation. The identification of Causative organism was carried out by standard identification test. Among the risk factors breathlessness and temperature instability were significant. Among the clinical features 45% of neonates had poor feeding and 31% had a birth weight less than 2.5kg. In this study, Out of 84 clinical neonatal sepsis 7(8.3%) were culture positive. Blood Culture and sepsis screen should be carried out in neonates suspected of sepsis. However culture report is available only after 5-7 days. Sepsis is common in new born with non specific symptamatology causing difficulty in diagnosis. Early and prompt detection and appropriate treatment in neonatal sepsis can significantly reduce morbitity and mortality. Present research explains the prevalence of neonatal sepsis in NICU and the causative various etiological agents were characterized.